Театрализованная деятельность как средство развития воображения у младших школьников с ЗПР на уроках литературного чтения - Кузьменко, Ю.П. (My University, 2016)
The article highlights the importance of the imagination of younger schoolboys with a delay of mental development through theatrical activity at lessons of literary reading. The value of theatrical activities for the development of the imagination of younger schoolboys with mental retardation is that this activity allows children to set straight the creative task, to give the child a task to create a new image, do it yourself. The author argues that the development of the imagination of younger schoolboys with a delay of mental development is complex and involves the use of means of theatrical activities in each lesson literary reading. Proposals contained in the article are practical and can be used in correctional work with children with mental retardation.
Keywords: mental retardation; a junior high school student; imagination; theatrical activities